A case report of hemothorax due to intrathoracic variceal rupture linked to Budd-Chiari syndrome - Yue Hu; Zaichun Deng; Yongbin Chen; Tingting Wu (BMC Pulmonary Medicine)
Abstract Background Budd-Chiari syndrome (BCS) is a hepatic venous system disease caused by obstruction of the hepatic blood flow outflow tract. The definition of hemothorax is that blood accumulates in the chest cavity, and the hematocrit value of the effusion exceeds 50%. Hemothorax caused by intrathoracic variceal rupture associated with BCS is rare. Case presentation A 43-year-old female patient with just 69 g/L hemoglobin, complaining of shortness of breath for 2 days, was admitted to gastroenterology department. The chest computed tomography (CT) revealed right pleural effusion and contrast-enhanced CT in portal venous phase revealed portal hypertension and multiple tortuous veins. The ratio of red blood cells to white blood cells in bloody pleural effusion was about 500:1, and the neuron-specific enolase (NSE) and cytokeratin 19 fragment antigen 21 − 1 (CYFRA21-1) in the pleural effusion were significantly increased. Therefore, the patient was transferred to the respiratory medicine department to exclude malignant pleural effusion. The enhanced chest CT reexamination showed a continuous enhanced soft tissue-like lump in the thoracic cavity, which was a varicose vein. The vascular interventional physician reviewed the contrast-enhanced CT in portal venous phase to see a stenosis between the hepatic vein and the inferior vena cava, so BCS was suspected. Vascular interventional surgery was performed, and identified obstructed blood flow at the upper end of the inferior vena cava, which significantly improved after thrombolysis. Therefore, the intrathoracic variceal rupture linked to BCS was the source of the patient’s pleural effusion. Conclusions when there is unexplained bloody pleural effusion and the tumor index of pleural effusion increases, thoracoscopic pleural biopsy should not be blindly performed, and pleural effusion caused by vascular rupture should be further excluded.